Assessment of the utility of platelet indices to diagnose clinical benign prostatic hyperplasia in dogs - Hosseinpour, Hediyeh; Ahmadi-hamedani, Mahmood; Masoudifard, Majid; Shirani, Darush; Narenj Sani, Reza (Frontiers in Veterinary Science, 2022)
Platelet indices changes in severely ill people and in dogs with inflammation are compatible findings. This study aimed to compare platelet indices between dogs with clinical benign prostatic hyperplasia (BPH) and healthy controls. Additionally, to determine whether there is a correlation between the relative prostatic size (Srel) and the platelet indices in BPH dogs. Thirty-five adult intact male dogs of different breeds were allocated to the experimental groups: dogs with clinical BPH (groups A; n = 24; median age of six years; the median weight of 8.50 kg) and healthy dogs (group B; n = 11; median age 5.50 years; the median weight of 7.00 kg) based on physical examination, clinical signs, and Srel detected by ultrasonographic findings. The individual prostatic volume (IPV) was divided by the expected prostatic volume (EPV) to determine the relative prostatic size in dogs over four years old. Platelet indices were compared between the two groups, and a correlation between Srel and these indices was calculated. The median Srel of dogs in group A was significantly higher (P =0.001), and the mean plateletcrit (PCT) was significantly lower (P = 0.003) compared with those in group B. Srel showed a significant negative correlation with PLT and PCT (r=-0.388; P = 0.02 and r=-0.402; P = 0.01). Receiver operating characteristic (ROC) analysis showed PLT and PCT thresholds for estimating Srel > 1 with 75% and 87.5% sensitivity and 71.82% and 63.64% specificity. The findings of this study support the use of platelet indices like PLT and PCT to detect clinical BPH in dogs. However, more research is needed to confirm their utility in conjunction with other previously described diagnostic factors.